15th International Conference on Concentrator Photovoltaic Systems (CPV-15) 2019
DOI: 10.1063/1.5123839
|View full text |Cite
|
Sign up to set email alerts
|

SiOxNy:B layers for ex-situ doping of hole-selective poly silicon contacts: A passivation study

Abstract: Passivating the contacts of crystalline silicon (c-Si) solar cells with a polycrystalline silicon layer (poly-Si) on a thin oxide (SiOx) film allows to decrease the recombination current at the metal/c-Si interface. In this study, an ex-situ doping method of poly-Si is proposed, involving a SiOxNy:B layer as a dopant source. In this study, we compare the properties (crystallinity of the deposited layer, doping profile and surface passivation properties) of the resulting ex-situ doped poly-Si(B) layer with our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a previous study, we reported on an original ex-situ doping process of the poly-Si/SiOx contacts [18]. This process relies on the deposition of an intrinsic Si layer by PECVD, which is ex-situ doped through the deposition of a B-rich dielectric layer followed by an annealing step at high temperature (700-850 °C).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported on an original ex-situ doping process of the poly-Si/SiOx contacts [18]. This process relies on the deposition of an intrinsic Si layer by PECVD, which is ex-situ doped through the deposition of a B-rich dielectric layer followed by an annealing step at high temperature (700-850 °C).…”
Section: Introductionmentioning
confidence: 99%